Selection of girls for canoe slalom on the basis of morphological and functional indicators during puberty - Okun, D.; Korolova, M.; Stadnik, S.; Rozhkov, V.; Mulyk, K.; Grynova, T.; Kalmykova, Y.; Bondar, A.; Petrenko, I. (Journal of Physical Education and Sport, 2020)
The article presents the compliance of anthropometric indicators of athletes specializing in canoe slalom. The problem of orientation and selection has long since become an independent science. Predicting the possibilities of a child or adolescent, the coach sets himself the task of a reasonable search for talented individuals with the hope of successful, in the future a narrow specialization. The problem of improving sports orientation has now found great support from specialists of various profiles both in our country and abroad. Despite the abundant data available, the problem of selection and orientation of the most talented people as an independent direction is in the stage of constant search, improvement and further development.An anthropometric survey of girls aged 9- 12 years old, who go in for rowing and canoeing, was carried out. The survey of girls aged 9-12 years old, who engaged in canoe slalom, allowed to form a kind of rower model based on anthropometric indicators.The agerelated dynamics of the development of morphological and functional indicators of girls during puberty was revealed. Informative criteria for assessing young female athletes in the selection for canoe slalom are proposed.As an informative criterion for assessing young athletes in the selection in canoe slalom, it is advisable to use Popescu tests, which allow to determine the main parameters of a person. These include body length, torso and arm length, arm span, as well as for kayakers (sitting body length with arms outstretched,) and for canoeists (kneeling body length with arms outstretched).For canoe slalom, should select young athletes of taller stature and with a longer body (excess height is provided due to the length of the body).When selecting, you can also use relative indicators of morphological development: female kayakers should have a greater ratio of body length to the length of the upper and lower extremities, canoeists should have a greater ratio of arm length to body length and leg length to body length.It was found that the majority of the surveyed girls aged 9-12 years old belonged to the average (44.1%) and above average (50%) levels of morphological development.